The Influence of Intellectual Capital Disclosure, Economic Value Added Analysis, and Inclusion of Warrants on the Level of Underpricing in Shares - Faisal, Muhammad; Wirawan Yasa, Gerianta (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
The underpricing phenomenon often occurs when a company conducts an initial public offering or commonly known as IPO (Initial Public Offering). This condition causes stakeholders receive not enough information for assessing the company value. This study aims to analyze the effect of intellectual capital disclosure, economic value added, and inclusion of warrants on the level of underpricing of shares. This research was conducted in all companies that conducted IPOs on the Indonesia Stock Exchange (IDX) in the period 2012-2014. The number of samples taken was 60 companies, with a purposive sampling technique. The data analysis technique used is multiple linear regression. The results of testing the partial test hypotheses found that intellectual capital disclosure variables negatively affect the level of underpricing, while the variables of warrants participation have a positive effect on the level of underpricing. The economic value added variable does not affect the level of underpricing. Keywords : Initial Public Offering  (IPO), Underpricing, Economic value added, Warrant.